Optimal Bundling Strategy for a Retail Platform Under Agency Selling - Guo, Xiaolong; Zheng, Shengming; Yu, Yugang; Zhang, Fuqiang (Production and Operations Management, 2021)
Bundling strategies have been widely adopted by online retail platforms that use agency selling, where suppliers pay a commission fee to the platform to gain access and sell directly to consumers. We study the optimal bundling strategy for a retail platform through which two independent suppliers distribute their products. The suppliers first set their product prices, and, subsequently, the platform decides whether to offer the two products as a bundle and, if so, the price of the bundled product. By analyzing a two‐stage Stackelberg game, we find that the platform adopts the bundling strategy only when the commission rate and the product prices are sufficiently high. The existence of the bundling option does not affect the suppliers’ optimal pricing decisions if the product costs are either above a high threshold or below a low threshold. However, the suppliers may strategically raise the retail prices to induce the platform to offer bundled products when the marginal costs are in the medium range. The strategic interaction between the platform and suppliers leads to interesting insights into the bundling problem. For example, the retail platform may not prefer a high commission rate (i.e., a greater bargaining power) if the platform has the option to provide the bundled product. Additionally, the platform having even the possibility of bundling may hurt the platform's profit, but it always benefits the suppliers.